حجــــية حــكم التحكيم التجاري الـــــــــــــــدولي - بالعيد حياة; ذهب الزهرة (University of Eloued جامعة الوادي, 2023)
التحكيم التجاري الدولي هو بديل القضاء ومسلك الأطراف متفاديين به تعقيدات القضاء وطول إجراءاته ، فالتحكيم التجاري هو نظام مبدأه إرادة الأطراف لإحالة نزاعاتهم إلى هذا النظام ، لينتهيفي الأخير بصدور حكم فاصل قي النزاع كما يتوجب توافر الحكم على شروط لصحته وسلامته لتصدره في الاخير بالإعتراف من قبل الجهات القضائية المختصة بذلك والإعلان بأن الحكم الذي صدر صحيح وملزم للأطراف ويكتسب حجية الشئ المقضي فيه ولا يتسنى للطرف الذي لم يكن الحكمقي صالحه إثارة النزاع من جديد، إلا أن حكم التحكيم يتعرض للطعن بالبطلان وفقا لحالات محددة على سبيل الحصر وتجعل حكم التحكيم محل البطلان مما يؤثر ذلك على حجية الحكم التحكيمي .International commercial arbitration is an alternative to litigation and a route for parties to avoid the complexities and length of court proceedings. Commercial arbitration is a system based on the parties' will to refer their disputes to this system، which ultimately results in a binding decision in the dispute. For the decision to be valid and enforceable، it must meet certain conditions and be recognized by the competent judicial authorities. The decision is then declared valid and binding on the parties and acquires the force of law. The party who did not benefit from the decision cannot re-raise the dispute. However، an arbitral award may be challenged for invalidity according to specific and limited circumstances، rendering the award invalid and affecting its enforceability. Furthermore، the competent authorities may either agree or disagree with the invalidity of the arbitral award.
مذكرة ماستر
Keywords: التحكيم - الحكم التحكيمي –الاطراف- الاعتراف بالحكم التحكيمي –الطعن بالبطلان - حجية الشيء المقضي فيه .; Arbitration، Arbitral Award، Parties، Recognition of Arbitral Award، Challenge of Arbitral Award and its Validity.